In vivo biomolecular imaging of zebrafish embryos using confocal Raman spectroscopy - Håkon Høgset (Nature Portfolio, 2020)
Raman spectroscopic imaging (RSI) can provide information on the chemical composition of a sample, but application to living organisms has lacked sufficient spatial resolution and signal strength. Here the authors apply confocal RSI to whole-mount zebrafish embryos to distinguish different infectious bacteria and to living zebrafish embryos to monitor the wound healing process.